Procreative health and surrogacy. The perverse effects of the prohibition (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The essay examines maternity surrogacy as a method of medically assisted procreation practicable in a controlled health context to remedy pathologies that prevent the woman from becoming pregnant. In this perspective, the author examines the consequences of the prohibition of surrogacy and identifies a space of admissibility for solidary gestation for others, considering the reasons that justify the crime.
Keywords: medically assisted reproduction; Rokitansky syndrome; surrogacy; parental responsibility; best interest of the child